PENERAPAN PROGRAM MUHADATSAH DALAM MENINGKATKAN MAHARAH KALAM SISWA KELAS 7 DI SMP MUHAMMADIYAH 3 BANDAR LAMPUNG - Halimatussa’diah; Ahmad Nur Mizan; Zulhannan; Adam Malik (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the implementation of the Muhadatsah program in improving the maharah kalam of seventh-grade students at SMP Muhammadiyah 3 Bandar Lampung. This research employed a descriptive qualitative approach with a case study design. Data were collected through observation, semi-structured interviews, and documentation involving Arabic language teachers, school principals, and seventh-grade students as research subjects. The results showed that the Muhadatsah program was implemented through simple dialogues, pair conversations, group discussions, and direct Arabic speaking practices in the classroom. The teacher acted as a facilitator by providing conversation examples, correcting pronunciation, and motivating students to speak Arabic confidently. Students’ participation and responses toward the Muhadatsah program were generally positive, as students became more active, enthusiastic, and confident in participating in Arabic conversations. The program also contributed to improving students’ speaking fluency, vocabulary mastery, courage, and self-confidence in using Arabic. However, some students still experienced difficulties due to limited vocabulary mastery and lack of confidence when speaking independently. Overall, the Muhadatsah program can be considered an effective strategy for improving students’ maharah kalam when implemented consistently, communicatively, and supported by an active learning environment.